2012
DOI: 10.1007/s00216-012-6120-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dialysis and solid-phase extraction for isolation and concentration of dissolved organic matter prior to Fourier transform ion cyclotron resonance mass spectrometry

Abstract: We compare two methods, solid-phase extraction (SPE) and dialysis, commonly used for extraction and concentration of dissolved organic matter (DOM) prior to molecular characterization by electrospray ionization (ESI) and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry. Spectra of DOM samples from Minnesota and Sweden peatlands that were extracted with styrene divinyl benzene polymer SPE sorbents included ions with formulas that had higher oxygen to carbon (O/C) ratios than spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 26 publications
4
58
0
2
Order By: Relevance
“…S3B). This difference between the DBE and DBE−O distributions indicates that bog DOM contains more hydrophilic, oxygen-rich compounds than fen DOM, and that a larger portion of the unsaturation in bog DOM is due to C=O bonds (mostly from carboxylic acid) than in fen DOM (41,42). The higher oxygen content of bog DOM, as evidenced by both its DBE/DBE−O distributions and its higher O/C ratios relative to fen DOM, indicate that bog DOM has a higher oxidation state than fen DOM.…”
Section: Resultsmentioning
confidence: 99%
“…S3B). This difference between the DBE and DBE−O distributions indicates that bog DOM contains more hydrophilic, oxygen-rich compounds than fen DOM, and that a larger portion of the unsaturation in bog DOM is due to C=O bonds (mostly from carboxylic acid) than in fen DOM (41,42). The higher oxygen content of bog DOM, as evidenced by both its DBE/DBE−O distributions and its higher O/C ratios relative to fen DOM, indicate that bog DOM has a higher oxidation state than fen DOM.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds in DOM are distributed over a wide range of ionization efficiency. Ionization of the low-efficiency compounds will be suppressed with the increase of the high-efficiency compounds [33,34], limiting the detection of compounds with low ionization efficiency at low concentration [24,34]. Conventionally, one-step elution uses an organic solvent such as methanol to elute all the DOM components into one sample [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have observed that a great number of compounds in DOM such as highly oxygenated tannin-like molecules [22,23], nitrogenous compounds with high hydrophilic character [23], and fatty-acid-like molecules [24] are preferentially lost during the single-step SPE procedure for a variety of SPE sorbents, such as XAD, C 18 and PPL [19,22e26]. To solve this problem, combinations of different isolation methods such as dialysis and SPE [24], ultrafiltration and SPE [25] or SPE with a combination of different sorbents [19,23,26] have been attempted recently in order to obtain a more accurate molecular representation of DOM. Nevertheless, the combination of different isolation methods is highly laborious, time-consuming, and hard to optimize and standardize.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on current isolation methods, the combination of multiple isolation approaches will provide the greatest recovery of DON. We direct the reader to several studies that compare or review isolation methods for a more thorough discussion (Aluwihare and Meador, 2008;Dittmar et al, 2008;Mopper et al, 2007;Simjouw et al, 2005;Tfaily et al, 2012).…”
Section: Don Isolation Methodsmentioning
confidence: 99%